Laddie: A True Blue Story - Stratton-Porter, Gene, 1863-1924 (Salt Lake City, UT : Project Gutenberg, 1995)
"Laddie: A True Blue Story" by Gene Stratton-Porter is a fictional narrative likely written during the early 20th century. The story centers around the relationship between two characters: Laddie, an older brother who embodies love and adventure, and his younger sister, affectionately referred to as Little Sister. Their bond is highlighted through their innocent conversations and imaginative escapades, reflecting themes of family loyalty and the tenderness of childhood. The beginning of the story introduces us to Little Sister as she interacts with Laddie, who enlists her help in delivering a letter to a mysterious Fairy Princess he has invited to their Big Woods. Initially filled with excitement about the secret mission, Little Sister's expedition showcases her deep admiration for Laddie, who is portrayed as a protective and charismatic figure in her life. As she navigates her journey through the woods, readers are drawn into her vivid imaginative world, where the lines between reality and fantasy blur. The opening pages establish a charming atmosphere enriched with whimsical elements, suggesting that the book will explore themes of adventure, magic, and family dynamics as the story unfolds. (This is an automatically generated summary.)
Release date is 1995-06-01
Keywords: Didactic fiction; Indiana -- Fiction